Murtad Sebelum Baliqh dan Kaitannya Dengan Kewarisan Dalam Pendangan Ulama Fiqh - Hasbi, Alimuddin (Siyasah Wa Qanuniyah, 2023)
This paper discusses the views of Islamic scholars (ulama fiqh) on apostasy before reaching the age of maturity (baliqh) and its relation to the inheritance of the wealth left by the deceased. There is a difference in understanding between the Hanafi and Shafi’i schools of thought regarding the legal status of apostasy before baliqh in relation to inheritance. The issues addressed in this paper include the perspectives of both schools on apostasy before baliqh and its connection to inheritance, whether a person who commits apostasy before baliqh is entitled to inherit, and the evidences cited by each school. This study aims to explain the differences in the Hanafi and Shafi’i schools of thought regarding apostasy before baliqh and their stance on inheritance. The research employs a qualitative descriptive method with a library-based literature review approach. The findings indicate significant differences between the Hanafi and Shafi’i schools. According to the Hanafi school, apostasy before baliqh is considered valid, and the person who commits apostasy is not entitled to inherit.